2016
DOI: 10.5012/jkcs.2016.60.5.310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrochemical Oxidation-Reduction Cycles on Surface Structures and Electrocatalytic Oxygen Reduction Activity of Au Electrodes

Abstract: ABSTRACT. Oxidation-reduction cycling (ORC) procedures are widely used for cleaning nanoparticle surfaces when investigating their electrocatalytic activities. In this work, the effect of ORC on the surface structures and electrocatalytic oxygen reduction activity of Au electrodes is analyzed. Different structural changes and variations in electrocatalysis are observed depending on the initial structure of the Au electrodes, such as flat bulk, nanoporous, nanoplate, or dendritic Au. In particular, dendritic Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…A similar phenomenon was also found in the study of the roughened surface for optical application as surface-enhanced Raman spectroscopy (SERS) substrate [30,33]. It also indicated that when the degree of oxidation-reduction in the gold surface became greater, the surface changes became more rapid, thus resulting in a swifter enhancement of oxygen reduction catalytic activity [34]. Precipitation and ionization in the solution may occur.…”
Section: Orc Treatment and Mechanismsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar phenomenon was also found in the study of the roughened surface for optical application as surface-enhanced Raman spectroscopy (SERS) substrate [30,33]. It also indicated that when the degree of oxidation-reduction in the gold surface became greater, the surface changes became more rapid, thus resulting in a swifter enhancement of oxygen reduction catalytic activity [34]. Precipitation and ionization in the solution may occur.…”
Section: Orc Treatment and Mechanismsupporting
confidence: 64%
“…Polishing treatment had significantly generated more uniform Au particles size and density after ORC treatment by the average height of about 50-100 nm and the length of approximately 50-150 nm over the Au substrate (Figure 3C). The outcomes signify the crucial role of polishing and cleaning the substrate to create a homogenous foundation and particle size control for Au growth [34]. Moreover, the largely homogenous surface resulting from polishing facilitates the well-scattered penetration of Au ions during the electrochemical ORC, where such actions will likely be hindered in the randomly roughened and dirty non-polished surface.…”
Section: Morphological and Topological Studies Of The Orc Engineered ...mentioning
confidence: 99%
“…The SEM image of the as‐synthesized aAuNPs (without purification) is shown in SI Figure S2. Purified nanotriangles form a specific arrangement, in which many electrochemically active edges are exposed to the electrolyte solution . Appropriate centrifuging programme allowed to remove most of the colloidal gold from the solution, SI Figure S3, S4.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure-oxidation-reduction cycling (ORC)-is known as an excellent mean for activation of electrode surface without changing its topography. Although the corners of nanoplates round slightly during the process, such structural changes do not diminish the oxygen reduction reaction catalytic activity [33].…”
Section: Cyclic Voltammetric Characterization Of Electrodesmentioning
confidence: 99%
“…6 Hence, both the "oxide layer" itself and the restructured metal surface after subsequent reduction of the surface oxide 4,5,[9][10][11][12] may modify electrocatalytic activities for given reactions. [13][14][15] Electro-oxidation of single crystalline and polycrystalline Au electrodes in different environments has been studied both electrochemically, [16][17][18][19][20][21][22][23][24] spectroscopically, 7,11,12,[25][26][27][28] and with imaging methods. 5,7,25,27,[29][30][31][32][33][34] Metal surfaces can be analyzed under ultrahigh vacuum (UHV) conditions and characterized using surface analytic techniques that are not accessible under atmospheric pressure like scanning electron microscopy (SEM) or low energy electron diffraction (LEED).…”
mentioning
confidence: 99%